The use of problem-based learning in an english for occupational purposes classroom among final semester students of Diploma in Office Management and Technology - Sim, Jacqueline Phek Kim (2006)
The purpose of this study was to investigate the use of PBL in an EOP classroom by determining, firstly, whether the use of PBL benefited the EOP respondents’ language skills, and secondly, whether there are any significant improvements in their language skills. The study also attempted to describe the respondents’ responses in the use of PBL in learning EOP. The respondents involved in this study were five final semester students from diverse backgrounds and different levels of English Language proficiency pursuing Diploma in Office Management and Technology at a local university in Sarawak. This study was conducted using the qualitative approach. Observation Checklists were used to collect data on the respondents’ oral language skills in their group discussions and presentations to ascertain if the use of PBL had benefited the respondents’ oral skills. Pretest and Posttest were administered at the beginning and the end of the study to determine if the process of learning EOP using PBL had benefited the respondents’ written language skills in the area of writing reply letters of complaints. The Posttest letters were also analysed for significant improvements in the language used by the respondents. Besides that, various types of Evaluation Forms were distributed to the respondents to obtain data on their responses towards the use of PBL in an EOP classroom. The findings from this study revealed that the respondents had responded positively towards the use of PBL. Their oral and written language skills had improved significantly. On top of that, their generic skills had also improved, and this would enhance their rate of employability upon graduation. All the results of this study pointed towards the fact that the use of PBL in an EOP classroom had benefited the respondents’ oral and written language skills.